Kualitas Pelayanan terhadap Loyalitas Pelanggan yang Dimediasi oleh Kepuasan Pelanggan Grab Bike di Kota Bandung - Nurfatmah, Siti; Sigarlaki, Faizal Fardhani (Journal of Management and Bussines (JOMB), 2024)
This research aims to determine the effect of Service Quality (Variable X) and Customer Satisfaction (Variable Z) on Customer Loyalty (Y). The method used in this research is quantitative methods with an associative descriptive approach. The type of data in this research is primary data collected using a questionnaire from respondents with predetermined characteristics. This research uses a validity test with the product moment formula and a reliability test with the Cronbach's alpha formula. After the data is collected, the data is processed through four stages of data processing, namely data coding, data entry, data editing, and data transformation. Was carried out using two multiple regression models and hypothesis testing to determine the relationship between the variables previously studied. Based on the results of the first multiple regression analysis, it can be seen that service quality has a positive effect on customer satisfaction, which can be seen from the significance value of 0.000 < 0.05. Then from the results of the second multiple regression analysis it can be seen that service quality and customer satisfaction have a positive effect on customer loyalty which can be seen from the respective significance values ​​of 0.003 and 0.000 <0.05. In conclusion, customer satisfaction mediates the influence of service quality on customer loyalty. Keywords: Service Quality, Customer Satisfaction, Customer Loyalty